Hubungan Perilaku Hidup Bersih Dan Sehat (PHBS) Ibu Dengan Kejadian Diare Pada Balita 0-5 Tahun Di Puskesmas Klasaman Kota Sorong - Helga Ruth P; I Wayan Badra (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2018)
The Relationship Between Clean and Healthy Life Behavior (PHBS) with Diarrhea in Toddlers (0-5 Years) in the Work Area of ​​the Sorong City Klasaman Health Center. According to the Indonesian Ministry of Health (2011) One application of PHBS in the household setting that can prevent the occurrence of diarrhea is the Handwashing with Soap (CTPS) behavior. CTPS is one of the pillars of the Community Based Total Sanitation (STBM) strategy, which is contained in the Decree of the Minister of Health of the Republic of Indonesia No. 852 / SK / Menkes / IX / 2008. The importance of CTPS has been understood to reduce the incidence of diarrhea by up to 47%. This is important to be known by the public in order to increase awareness to familiarize CTPS in everyday life. the incidence of diarrhea in children aged 0-5 years in January to March 2017 reached 80 cases (PKM Klasaman, 2017). The purpose of this study was to determine the relationship between Clean and Healthy Behavior (PHBS) with Diarrhea in infants (0-5 years) in the working area of ​​the Sorong City Klasaman Health Center. The research design is a Crossectional Study, the sample uses a total population of 81 respondents, tested with Chi-Square. The results of the study there is a relationship between the behavior of using clean water with the incidence of diarrhea in children 0-5 years in the Sorong City Klasaman Health Center with a value of 0.002 <α = 0.05. There is no relationship between the behavior of using healthy latrines with the incidence of diarrhea in children 0-5 years in the Sorong City Klasaman Health Center, the value of which is 0.253> α = 0.05. There is no relationship between the behavior of using clean water and the incidence of diarrhea in children 0-5 years in the Sorong City Klasaman Health Center, a value of 0.110> α = 0.05.